Model Prediksi Kebutuhan Air Bersih Berdasarkan Jumlah Penduduk di Kawasan Perkotaan Sentul City - Suheri, Asep; Kusmana, Cecep; Purwanto, Moh Yanuar J; Setiawan, Yudi (Jurnal Teknik Sipil dan Lingkungan, 2019)
This research aims to create a model for predicting clean water need in the urban area Sentul City currently and next 30 (thirty years). To create the model, it is required data which are useful for forecasting the inhabitant number year to year. There are some general-used models for forecasting the inhabitant number, including to arithmatic, exponential, and least square method. The inhabitant number forecast in this research used an exponential method, as recommended in the Guidance of River Area Water Resource by Directorate General of Water Resource in 2001. The researcher used the software Stella 9.0.1 for simplifying the modeling process, projecting the inhabitant number, predicting the clean water need, and figuring the graphics. Besides this software, Excel programme was also used. According to data analysis result, the equation models to predict water need (m3/year) in Sentul City are stated as follows; for rural area inhabitants: YDn = 1 927 309 (1 + 0.0303)n; for urban area inhabitants: YKn = 1 808 940 + 217 248*n;  and for total inhabitants: YSCn = YDn + YKn.Keywords: inhabitant number, geomeric method, clean water need prediction